Holy See vision of the global legal and political order and its critical analysis - Rudinskas, Aurimas (Religija ir kultūra, 2024)
As the influence of the Holy See in the international arena increases due to the ongoing transformation of international society, resulting from the increasing influence of nongovernmental organizations and other non-state actors, it becomes important to know what legal and political mechanisms operating on a global scale, the Holy See proposes to solve the most pressing problems of humanity. It was found that between 1939 and 1956 the Holy See proposed the idea of an international legal peace institution and publicly supported the idea of a world government or world federation promoted by the World Federalist Movement. Both must ensure global security and peace. Since 1963 until 2015 the Holy See promoted the idea of a world political authority with the power, institution and means to effectively solve global problems. The research shows that these projects contain features of social contract theory. The reform of the United Nations organization, giving it more powers, is considered the first step towards the emergence of a global public authority.